Utilization of Probiotics, Fermented Beverages, and Aspergillus niger in Drinking Water on Performance and Digestive Quality of Broilers (Gallus domesticus) - Rahmatillah, Zumara; Allaily, Allaily; Firdus, Firdus (Jurnal Agripet, 2025)
Probiotics and Aspergillus niger are known to play a role in supporting poultry growth and improving digestive tract health. This study aimed to determine the effectiveness of probiotics in the form of fermented drinks and A. niger in improving broiler chicken productivity and digestive tract health. The research was conducted at the LLP (Livestock Field Laboratory) of Syiah Kuala University, while the histological observations of the chicken intestinal villi surface were carried out at the Laboratory of Animal Structure and Development, Faculty of Mathematics and Natural Sciences, Syiah Kuala University. The method used in this study was a Completely Randomized Design (CRD) with 5 treatments (drinking water (control), antibiotic, 5% kefir, 5% Yakult, 2% A. niger) and 3 replications. The experimental animals used were broiler chickens from DOC to harvest age, with an initial average body weight of 5157 g, totalling 75 individuals reared for 4 weeks (30 days). The parameters measured included performance (body weight gain, feed intake, water intake, feed conversion ratio (FCR), defined as the ratio of feed required to produce one unit of body weight, and feed efficiency ratio [FER], defined as the ratio of body weight gain to feed intake), as well as histological features of the intestinal villi (height, apical width, basal width, and total surface area). Data were analysed using ANOVA at a 95% significance level, followed by Duncans multiple range test (P0.05). The results showed that the 5% kefir group (P2) had the best performance, with feed intake of 1294.25194.21 g/bird, feed conversion of 0.90330.13 g/bird, water intake of 4673.1769.06 ml/bird, body weight gain of 1792.2632.34 g/bird, and feed efficiency of 9.48670.74%. Histological analysis showed that the intestinal villi size was highest in the 5% kefir group (P2), with an average villi height of 969.9644.64 m, apical width of 110.9912.23 m, basal width of 106.9712.41 m, and total surface area of 1076.9354.26 m.